Household responsibilities and personal goals of first born college students from single -parent and two-parent families in Metro Manila - Bitana, Sharmine Mae D.; Estrella, Roda Tessa L.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philiuppines Diliman, 2010)
ABSTRACT In single-parent families, children acquire new responsibilities in the household that are primarily of their parents. Firstborns, in particular, can be assigned with family responsibilities and be perceived responsible by their parents in concerns regarding their household and their siblings. This qualitative study explored the household responsibilities and personal goals of firstborn college students from single-parent and two-parent families. Sixty firstborn college students, purposively sampled, were interviewed using the interview guide that was developed by the researchers. The semi-structured interviews, recorded and transcribed, were analyzed using thematic analysis. Results showed that family structure does not determine household responsibilities and personal goals of firstborn adolescents. Their performance of household chores varies according to the presence of a paid helper within the household. Short-term and long-term goals of firstborn adolescents do not vary according to their family structure but according to the socioeconomic status of their family.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: First-born children